2023
DOI: 10.3390/jcm12082870
|View full text |Cite
|
Sign up to set email alerts
|

Bruch’s Membrane: A Key Consideration with Complement-Based Therapies for Age-Related Macular Degeneration

Abstract: The complement system is crucial for immune surveillance, providing the body’s first line of defence against pathogens. However, an imbalance in its regulators can lead to inappropriate overactivation, resulting in diseases such as age-related macular degeneration (AMD), a leading cause of irreversible blindness globally affecting around 200 million people. Complement activation in AMD is believed to begin in the choriocapillaris, but it also plays a critical role in the subretinal and retinal pigment epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 299 publications
0
6
0
Order By: Relevance
“…Bruch’s membrane (BrM) is a thin layer of extracellular matrix, which is a selectively permeable membrane between the retina and choroid and regulates the exchange of nutrients, oxygen, minerals, and by-products of the visual cycle through passive diffusion, influenced by the weight, size, and shape of the diffusing molecule. While some complement proteins, such as FHL-1, factor D, and C5a, are allowed to diffuse through, most complement proteins (including the low-molecular-weight C3a) are unable to do so [ 39 , 40 ]. Finally, before any drug reaches the retina, it must pass the retinal pigment epithelium (RPE), which also forms the outer blood–retina barrier (BRB), regulating drug permeability via physicochemical properties, such as molecular weight, lipophilicity, protein binding, and concentration gradient [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bruch’s membrane (BrM) is a thin layer of extracellular matrix, which is a selectively permeable membrane between the retina and choroid and regulates the exchange of nutrients, oxygen, minerals, and by-products of the visual cycle through passive diffusion, influenced by the weight, size, and shape of the diffusing molecule. While some complement proteins, such as FHL-1, factor D, and C5a, are allowed to diffuse through, most complement proteins (including the low-molecular-weight C3a) are unable to do so [ 39 , 40 ]. Finally, before any drug reaches the retina, it must pass the retinal pigment epithelium (RPE), which also forms the outer blood–retina barrier (BRB), regulating drug permeability via physicochemical properties, such as molecular weight, lipophilicity, protein binding, and concentration gradient [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These components act as molecular sieves, facilitating the exchange of nutrients, oxygen, minerals, and byproducts of the visual cycle between the RPE and the choroidal capillaries. They also contribute to distinguishing the retina from the somatic circulation [ 35 ]. Furthermore, BM is believed to offer physical support for RPE cell adhesion, migration, and differentiation [ 36 ].…”
Section: Tissue Engineering Materialsmentioning
confidence: 99%
“…Similarly, flow abnormalities in the choriocapillaris surrounding the atrophic lesions may be connected with the escalation in GA growth rate. Moreover, in cases of eyes with a quiescent choroidal neovascularization, there is considerably higher risk of becoming exudative (15)(16)(17)(18) compared to eyes lacking a precursor quiescent choroidal neovascularization.…”
Section: Vascular and Other Features Choroid Vascular Structures Alte...mentioning
confidence: 99%
“…However, high-resolution ophthalmic imaging revealed that the study of BrM appears fundamental for understanding of AMD pathogenesis, because BrM is responsible for key transport functions and constitutes structural support to RPE, while, in the process of aging, it undergoes detrimental structural changes including thickening, decreased elasticity, and reduced permeability. Thus, perception of transit of complement proteins and vectors across BrM and RPE is also pivotal for the efficacy of therapies based on application of complement inhibitors and regulators [ 15 ]. In cases of therapeutic use and possible clinical applications, certain biomaterials are praised for their potential in drug release control, redistribution, and the establishment of long-term delivery.…”
Section: Introductionmentioning
confidence: 99%